Reproductive and sexual rights: confidentiality and hiv/aids in Chilean adolescents - Valenzuela Rivera, Ester; Casas Becerra, Lidia (Acta Bioethica, 2007)
Adolescents face cultural and institutional obstacles when visiting health care services searching for sexual and reproductive health care. Youngsters who consider themselves at risk for HIV/AIDS undergo discrimination due to socioeconomic reasons, and their right to health care access is infringed under a confidential framework. The principle of progressive autonomy and the evolution of their faculties is ignored. The International Convention for Child's Rights, ratified by Chile, provides a legal framework for dialogue and for a new relationship between adolescents with their family, the State and society, establishing a new paradigm to consider infants and adolescents as subjects to rights.